Women's emancipation writing at the fin de siècle - Shabliy, Elena V.,Kurochkin, Dmitry,O'Donnell, Karen (Routledge, Taylor & Francis Group, 2019)
Introduction: The New, but New with G*d / Elena V. Shabliy – Women's Labor Activism in the Progressive Era and Marie Van Vorst's Amanda of the Mill as a Social Propaganda Tool / Emine Gecgil –
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Literature; Modern; Literature; Sex role in literature; Feminism and literature; Decadence (Literary movement)